The Wound and the Womb: The Politics of Reproduction and Repair in Tsitsi Dangarembga’s Tambudzai Trilogy - Mehra, Gayatri (Research in African literatures, 2025)
My article places Tsitsi Dangarembga’s Tambudzai trilogy’s representation of the psychological wounds of (post)coloniality in conversation with Frantz Fanon’s work that politicized the psychological dimension of human (social) life. While both Fanon and Dangarembga ascribe a fundamental importance to the realm of the “subjective”—Fanon’s term—in thinking about social and political life, the trilogy, I argue, introduces a feminist perspective to investigate the (mis)fortunes of the psychological. More specifically, I contend that the trilogy descries the psychological through (to use Emma Dowling’s phrasing) “the lens of social reproduction.” Such a standpoint, explicitly visible in This Mournable Body , helps Dangarembga establish that psycho-affective reproductive labor—the feminized, devalued, and invisibilized work of love and care—births and nurtures the psychological realm. My paper evinces the presence of this reproductive standpoint by tending to Tambu’s vexed relationship with her mother in the second and the third novels, one that finds closure through the crucial scene of the mother’s nervous breakdown in This Mournable Body . With this reproductive lens, I show that the trilogy, especially The Book of Not and This Mournable Body (the focus of my essay), illuminates that the absence of care is a necessary aspect of psychological wounding. In this way, the trilogy demonstrates that Fanon’s theorization is indispensable but limited as his theoretical framework does not account for the feminized psycho-emotional labor of care in his discussion of the causes of psychological distress. Finally, my essay also shows that This Mournable Body advances a feminist reparative imaginary that recognizes the political necessity of healing and repairing the psychological damage of coloniality and postcoloniality through collectivized practices of care. My essay avers that in linking—what Marxist-feminist scholars term—a “crisis of care” to the problem of postcolonial wounding, Dangarembga reimagines the Fanonian (masculinist) political tradition by inserting within it a feminist reparative politics.